The Long Noncoding RNA MALAT1 Induces Tolerogenic Dendritic Cells and Regulatory T Cells via miR155/Dendritic Cell-Specific Intercellular Adhesion Molecule-3 Grabbing Nonintegrin/IL10 Axis - Wu, Jian; Zhang, Hanlu; Zheng, Yang; Jin, Xiangyuan; Liu, Mingyang; Li, Shuang; Zhao, Qi; Liu, Xianglan; Wang, Yongshun; Shi, Ming; Zhang, Shengnan; Tian, Jinwei; et al. (Frontiers in Immunology, 2018)
By shaping T cell immunity, tolerogenic dendritic cells (DCs) play critical roles in the induction of immune tolerance after transplantation. However, the role of long noncoding RNAs (lncRNAs) in the function and immune tolerance of DCs is largely unknown. Here, we found that the lncRNA MALAT1 is upregulated in the infiltrating cells of tolerized mice with cardiac allografts and activated DCs. Functionally, MALAT1 overexpression favored a switch in DCs toward a tolerant phenotype. Mechanistically, ectopic MALAT1 promoted dendritic cell-specific intercellular adhesion molecule-3 grabbing nonintegrin (DC-SIGN) expression by functioning as a miR155 sponge, which is essential for the tolerogenic maintenance of DCs and the DC-SIGN-positive subset with more potent tolerogenic ability. The adoptive transfer of MALAT1-overexpressing DCs promoted cardiac allograft survival and protected from the development of experimental autoimmune myocarditis(EAM), accompanied with increased antigen-specific regulatory T cells. Therefore, overexpressed MALAT1 induces tolerogenic DCs and immune tolerance in heart transplantation and autoimmune disease by miR155/DC-SIGH/IL10 axis. This study highlights that the lncRNA MALAT1 is a novel tolerance regulator in immunity that has important implications in settings in which tolerogenic DCs are preferred.